2022
DOI: 10.1111/jocs.16575
|View full text |Cite
|
Sign up to set email alerts
|

Robotic mitral valve repair: A single center experience over a 7‐year period

Abstract: Background: We report the clinical and echocardiographic results of our experience in robotic mitral valve repair over a 7-year period. The outcomes of the earliest and the latest patients will be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Another study which reported mid-to long-term results after endoscopic robotic mitral valve surgery in 1,257 patients by Murphy and colleagues was excluded as 7% of patients underwent mitral valve replacement (not repair) and therefore did not meet inclusion criteria. Therefore, nine studies remained after fulfilling the pre-determined inclusion criteria (21)(22)(23)(24)(25)(26)(27)(28)(29), with a total of 3,300 patients undergoing RMVr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study which reported mid-to long-term results after endoscopic robotic mitral valve surgery in 1,257 patients by Murphy and colleagues was excluded as 7% of patients underwent mitral valve replacement (not repair) and therefore did not meet inclusion criteria. Therefore, nine studies remained after fulfilling the pre-determined inclusion criteria (21)(22)(23)(24)(25)(26)(27)(28)(29), with a total of 3,300 patients undergoing RMVr.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the nine included studies were retrospective observational case series or cohort studies (21,22,(24)(25)(26)(27)(28)(29), with only one study being prospective in nature (23) (Table 1). One of the included studies was a comparative cohort study comparing RMVr to conventional sternotomy (24), therefore, only data regarding the robotic group was included in the present study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The potential impact of ethnicity on robotic mitral valve repair Dear Editor, We read the article "Robotic mitral valve repair: A single center experience over a 7-year period," by Dr Maureen Klepper et al 1 with great interest. The main limitation identified in this report was the lack of consideration regarding the impact of ethnicity on outcomes following robotic mitral valve repair.…”
mentioning
confidence: 99%
“…Outcomes of the earliest and latest patients are compared. 1 The study identifies the following patient characteristics: Gender, age, BMI, co-morbidities, and smoking history. Although these factors are important in considering outcomes post valve repair, we believe that the impact of ethnicity following surgery should be further investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation